A test of environmental Kuznets curve for haze pollution in China: Evidence from the penal data of 27 capital cities. (20th December 2018) - Du, Gang; Liu, Shuzhan; Lei, Ni; Huang, Yong
Abstract: The mounting environmental crisis, especially the large-scale and continuous haze pollution, is the most pressing challenge for China during rapid urbanization process. This study is aimed at examining the relationship between haze pollution and economic growth, and its turning points for different regions in China based on the panel data of 27 capital cities and municipalities in China during 2011–2015. We constructed the parameter estimation model after conducting the unit root, cointegration and Hausman tests. Based on the basic and extended models, we find that the relationship between haze pollution and economic growth in China is not a typical inverted U-shaped Environmental Kuznet Curve (EKC). By introducing variables such as industrial structure, foreign trade, and energy intensity, this study demonstrates that adjusting industrial structure and improving energy efficiency are effective means for haze pollution control. Grouping regressions reveal that regional differences exist in the relationships between haze pollution and economic growth and their tuning points. For instance, there was a U shaped relationship for the central region, while there were inverted N shaped relationships for eastern, western, and northeastern regions. Policy implications are thus summarized for different regions in terms of balancing economic growth and environmental protection.